Argument between Mach and Einstein in the light of the philosophy of recetivism - Boczar, Janusz (Folia Philosophica, 2004)
The author clearly explains the nature of the argument between Mach, Einstein and Avenarius about the metaphysical status of being. It turns out that science and philosophy deliver separate solutions in this field. The author of the article proves that the ideas of recentivism explain these discrepancies completely. Contemporary science-competence trends reveal maximalistic tendencies. Meanwhile the author proves that with an acquisition of a recentivistic option - thus a reductionist option - one is capable of reconciling the results provided by science and philosophy. It is a very innovative methodological solution.